Penerapan Metode Hungarian dalam Penugasan Karyawan Casual pada Perusahaan BUMN - Sipni, Dawam Mussurur; Rarasati, Niken (Politeknik Negeri FakFak, 2025)
The Secretariat and Legal Department of a state-owned enterprise (BUMN)has an important role in ensuring compliance and efficient administrative management. The purpose of this study is to analyse the application of the Hungarian method in allocating non-permanent staff in the Secretariat and Legal Department. It is expected that by applying the Hungarian method, staff allocation can be more effective, thus supporting the secretarial function in document management and the legal department in handling legal issues. The results showed that the application of the Hungarian method not only accelerated the allocation process, but also resulted in a more optimal allocation of human resources, which ultimately improved the performance of the teams in the secretarial department and the legal department. The methods used in this study include quantitative and qualitative analyses as well as data collection through observation and interviews with stakeholders